A novel duplex plasma treatment combining plasma nitrocarburizing and plasma nitriding. (November 2016) - Miao, Bin; Chai, Yating; Wei, Kunxia; Hu, Jing
Abstract: In this study, a novel duplex treatment (DT) combining plasma nitrocarburizing (PNC) and plasma nitriding (PN) was primarily developed for AISI 1045 steel. The modified samples were investigated by optical microscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), microhardness test, and pin-on-disk tribotest. The results showed that the nitriding efficiency was remarkably improved by DT, and the compound layer was much thicker than that treated by PNC or PN alone. Furthermore, higher cross-sectional microhardness and significant enhancement of wear resistance were achieved. The possible enhancement mechanism could be the phase transformation of γ′ to ε, and the reduced amount of cementite could be because of the activating and ionizing effect of the subsequent PN on cementite. Highlights: A novel duplex treatment combining plasma nitrocarburizing and plasma nitriding was developed. The duplex treatment can increase the nitriding efficiency and compound layer thickness. It produces higher microhardness. The duplex treatment can significantly improve wear resistance.